2020
DOI: 10.3390/psychiatryint1020007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mindfulness and Sleep Quality is Mediated by Emotion Regulation

Abstract: Background: Sleep is critical to a person’s overall physical and mental health. The current study investigated the relationship between mindfulness and sleep quality, to determine if this relationship is influenced by emotion regulation and perceived stress. Method: Three hundred sixty-seven undergraduate students responded to five self-report measures, (1) The Cognitive and Affective Mindfulness Scale (CAMS-R), (2) The Impact of Event Scale (IES-R), (3) The Five Facet Mindfulness Questionnaire (FFMQ), (4) The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
5
12
0
Order By: Relevance
“…This study revealed that MBSR group training affects the sleep quality of postmenopausal women until one month after the intervention ( p < 0.001). The results of the present study are consistent with some studies [ 35 , 45 – 48 ]. Andersen et al(2013) assessed effect of mindfulness-based stress reduction on sleep quality among Danish breast cancer patients; their results showed that MBSR improved of sleep quality just after the intervention but no long- term effect (6–12 months) among these patients [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study revealed that MBSR group training affects the sleep quality of postmenopausal women until one month after the intervention ( p < 0.001). The results of the present study are consistent with some studies [ 35 , 45 – 48 ]. Andersen et al(2013) assessed effect of mindfulness-based stress reduction on sleep quality among Danish breast cancer patients; their results showed that MBSR improved of sleep quality just after the intervention but no long- term effect (6–12 months) among these patients [ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Talley et al (2020) in a comprehensive study revealed that a high level of intrusive thoughts, avoidance, and over-stimulation are associated with sleep quality. Mindfulness techniques due to improving awareness and reducing reaction to negative thoughts can help a person to sleep [ 48 ]. Of course, in the present study, the mediators of sleep quality have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…While cognitive reappraisal and/or suppression constitute an attempt to exert executive control over these runaway repetitive thoughts, and will modify the association between Suppression with self-reported sleep difficulty and no association with Reappraisal, 64,65 others have found a negative association between Reappraisal and sleep difficulty, 66 and yet others report that neither factor was associated with sleep difficulty. 67 Here we found that both tendencies correlated, albeit weakly, with subjective sleep reports, in the expected directions and consistent with the association between Reappraisal and Suppression with better vs. worse mental health, respectively. 68,69 It should be noted that the correlations between sleep measures and Suppression were larger than the correlations with Reappraisal, in line with reports of stronger associations between Suppression and psychopathology symptoms in posttraumatic stress disorder, 70 anxiety, and eating disorders.…”
Section: Discussionsupporting
confidence: 87%
“…Also, Individuals high in neuroticism exhibit lower sleep quality and frequently report unwanted wakefulness after sleep onset [55,56]. Vulnerability to psychological disorder is key to understanding differential stress responses to severe life events [57][58][59]. Depression are also one of the common causes of sleep disorders, with depressive symptoms accounting for more than 40% of insomnia cases [60].…”
Section: Discussionmentioning
confidence: 99%